Transforming Islamic Law in Indonesia from a Legal Political Perspective - Ahmad Yani; Megawati Barthos (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
This article aims to discuss the transformation of Islamic law in Indonesia. This research is qualitative in the form of a literature study with a political-law approach. The idea of this paper is based on a misunderstanding of Islamic law and Islamic law and fiqh. Issues related to the debate on the application of Islamic law in the contemporary era also contribute to thoughts in this paper. This paper concludes that the transformation of Islamic law into national law is a difficult task. This is because Indonesia is a multi-cultural, multi-ethnic, and multi-religious country. The most important reason is due to the variety of Muslim understanding of religious texts